2012
DOI: 10.5343/bms.2011.1083
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Hooking Location and Condition of Animals Captured with Pelagic Longlines: The Grand Banks Experiments 2002–2003

Abstract: experiments were conducted on the grand Banks of the north Atlantic ocean during 2002-2003 to evaluate the effect of circle hooks and mackerel bait on pelagic longline catches and bycatch, and compare the treatments to the industry standards at the time. circle hooks were 18/0, and both non-offset and 10° offset were used as separate treatments and compared to the 9/0 J-hook control hooks with 10°-30° offset. Bait treatment was mackerel (Scomber scombrus linnaeus, 1758), which was compared to the squid control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 7 publications
1
51
1
Order By: Relevance
“…Reported AVM of the former may be as low as c . 5–30% (Megalofonou et al , ; Epperly et al , ; Gallagher et al , 2014 a ; Campana et al , ; Gilman et al , ), but studies with greater sample sizes have generally reported AVM to be in the region of 35–56% (Beerkircher et al , ; Coelho et al , , ; Bromhead et al , ). These estimates of AVM are of a similar magnitude to that reported for L .…”
Section: Taxonomic Overview Of Elasmobranch Discard Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported AVM of the former may be as low as c . 5–30% (Megalofonou et al , ; Epperly et al , ; Gallagher et al , 2014 a ; Campana et al , ; Gilman et al , ), but studies with greater sample sizes have generally reported AVM to be in the region of 35–56% (Beerkircher et al , ; Coelho et al , , ; Bromhead et al , ). These estimates of AVM are of a similar magnitude to that reported for L .…”
Section: Taxonomic Overview Of Elasmobranch Discard Survivalmentioning
confidence: 99%
“…These estimates of AVM are of a similar magnitude to that reported for L . nasus , 21–44% (Coelho et al , ; Epperly et al , ; Gallagher et al , 2014 a ; Campana et al , ). Campana et al () also used PSATs to understand PRM, which allowed overall mortality to be estimated at 49 and 59% for I .…”
Section: Taxonomic Overview Of Elasmobranch Discard Survivalmentioning
confidence: 99%
“…The less exposed points of circle hooks reduce the probability of foul-hooking organisms. When ingested, J-shaped hooks tend to result in deep hookings, while circle hooks with little or no offset tend to catch in the corner of the mouth (Cook and Suski 2004;Curran and Beverly 2012;Epperly et al 2012;Clarke et al 2014;Parga et al 2015). Due to the prevalent hooking location, circle hooks might result in higher pre-catch 1 and haulback survival rates, make it easier for crew to remove all terminal tackle, and thus increase the probability of post-release survival for turtles released alive (Chaloupka et al 2004;Cooke and Suski 2004;Godin et al 2012;Serafy et al 2012;Swimmer and Gilman 2012;Parga et al 2015).…”
Section: Hook Shapementioning
confidence: 99%
“…Hook shape, however, likely has nominal effect on catch rates of hard-shelled turtles, which tend to get caught by ingesting the hook regardless of hook shape (e.g., Gilman 2011;Epperly et al 2012;Clarke et al 2014). For hard-shelled and leatherback turtles that ingest a hook, circle hooks result in a lower proportion of turtles swallowing the hook deeply, into the esophagus and deeper, and therefore likely result in a higher survival rate relative to J-shaped hooks.…”
Section: Hook Shapementioning
confidence: 99%
See 1 more Smart Citation